Increasing Understanding of Family Members We On Children In Early Childhood Education Aisyiah Wirogunan Through Learning Method Game Guess My Family - Suyahman, Suyahman (Universitas Negeri Semarang, 2016)
Motivating the selection of the title of this study is the existence of a fact that the majority of children in Early Childhood Education Aisyiah when asked by the teacher about the identity of family members generally confused or do not know even cried. This condition is scientifically interesting to examine why this is so. I was thinking whether the way the teacher when ask less humanist, or the language used by teachers are poorly understood or ask when the time is not quite right. My mind ultimately boils down to the method used by the teacher is less precise, that's why I made the decision to examine scientifically by choosing a method of game